Perancangan Alat Pengaduk Magnetik Berbasis Arduino Uno Atmega 328p - Indra Jaya; Di Ikhwal (PTE FTK UIN Ar-Raniry, 2023)
To stir and homogenize chemical solutions and other liquid substances, a magnetic stirrer is required. This study aims to create a magnetic stirrer device with three speed levels based on the Arduino Uno microcontroller. This stirrer tool is made up of a DC motor, a Microcontroller with the IC ATmega 328P, a speed control circuit, a buzzer, and an LCD display. The IC controller will initialize commands to the LCD circuit and the speed control circuit when the device is turned on, according to the tool's working principle. When the set timer button is pressed, the speed set menu appears; on the speed set menu, press the high, low, and normal buttons to select the speed.The motor's speed is controlled using the PWM principle, which involves setting the duty cycle to 25% (Low) for low speeds where the voltage supply to the DC motor is 1.25 volts, 60% for medium speed (Normal) where the voltage supply is 3 volts, and 100% for high speed (High) where the voltage supply is 5 volts. Then press the Start button to begin stirring. If the motor is turned on, the tool will run for a predetermined time ranging from 1 to 15 minutes. Then, press the required speed start button. Then, press the start button to begin stirring; if the motor runs, the stirrer tool will run for the duration specified. To determine the speed of a DC motor at low speeds. Low speed DC motor speed measurements yielded a speed of 2673 rpm, normal speed yielded a speed of 3294 rpm, and high speed yielded a speed of 4438 rpm. The buzzer will sound when the stirring process is complete.